Well channeling and water plugging method, plugging system thereof and preparation method of plugging system

By using a sealing system with high-temperature resistant inorganic curing agent, suspension stabilizer, thixotropy modifier and accelerator in heavy oil hot production wells, the problem of thermal degradation of sealing materials at high temperatures is solved, and efficient sealing of steam/water traversing channels is achieved, and the yield and safety of heavy oil hot production is improved.

CN119899647APending Publication Date: 2025-04-29CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311405828.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

During the hot production of heavy oil, high-temperature steam is prone to flow along the high-permeability zone or large pores, resulting in steam and water traversing, reducing the heat utilization rate of steam. In addition, existing temperature-resistant sealing materials are prone to thermal degradation at high temperatures, poor construction safety and insufficient sealing strength.

Method used

A sealing system including a temperature-resistant inorganic curing agent, a suspension stabilizer, a thixotropic modifier and accelerator is adopted. The system can effectively block the steam/water traversal channel at high temperatures through its high temperature resistance, high strength and strong thixotropic properties.

Benefits of technology

The sealing system can remain stable at a high temperature of 350°C, has high compressive strength and good thixotropic properties, and can effectively avoid formation water dilution and plugging agent throwback, significantly improving the yield of heavy oil hot production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899647A_ABST
    Figure CN119899647A_ABST
Patent Text Reader

Abstract

The invention provides a well channeling and water plugging method, a plugging system and a preparation method thereof. The plugging system comprises a temperature-resistant inorganic curing agent, a suspension stabilizer, a thixotropic modifier, an accelerant and a water phase, the temperature-resistant inorganic curing agent comprises any one or a combination of at least two of metakaolin, superfine slag powder or fly ash; the thixotropic modifier comprises nano silicon dioxide or fumed silica. The preparation method of the plugging system comprises the step of mixing materials of the plugging system to obtain the plugging system. The plugging system disclosed by the invention can tolerate the influence of underground high temperature, is high in plugging strength and relatively strong in thixotropic property, and solves the technical problems of channeling and water plugging of a heavy oil thermal production well.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field, and in particular to a method for sealing well channeling and blocking water, a blocking system thereof, and a preparation method thereof. Background Art

[0002] The development potential of heavy oil in the future will be huge. At present, heavy oil is mainly developed by thermal recovery, which requires injecting high-temperature steam into the well to heat the formation crude oil, reduce the viscosity of the crude oil and improve the fluidity of the crude oil.

[0003] However, most of the heavy oil thermal recovery blocks are high-porosity and permeability sandstone reservoirs. Due to the influence of factors such as reservoir structure, heterogeneity, burial depth and large difference in steam / heavy oil mobility ratio, the injection of high-temperature steam is prone to flow along high-permeability zones or large pores, resulting in steam channeling, poor oil layer heating effect and low steam thermal utilization rate. During the recovery process, due to the induction of steam channeling, formation water and condensed water enter the vicinity of the wellbore along the steam channeling channel, resulting in high water content in the oil well, and the steam channeling and water outlet channel need to be controlled.

[0004] At present, heat-resistant chemical plugging materials are mainly used for blocking and water blocking. The temperature of heavy oil steam injection can reach above 300℃, which requires high heat resistance of plugging materials. Conventional gel, foam system, pre-crosslinked particles and inorganic particles are not suitable for high-temperature well conditions in heavy oil thermal recovery due to their easy thermal degradation at high temperature, poor construction safety and plugging strength.

[0005] Therefore, it is necessary to develop materials that can effectively block steam / water channeling under high steam temperatures. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for sealing and plugging water in a well, a plugging system and a preparation method thereof. The plugging system cooperates with a temperature-resistant inorganic curing agent, a suspension stabilizer, a thixotropic modifier and a promoter, has the advantages of high temperature resistance, high strength and strong thixotropic performance, and can effectively increase the output of heavy oil thermal recovery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a plugging system for sealing wells and blocking water, the plugging system comprising a temperature-resistant inorganic curing agent, a suspension stabilizer, a thixotropic modifier, a promoter and an aqueous phase; the temperature-resistant inorganic curing agent comprises any one of kaolin, slag powder or fly ash or a combination of at least two thereof; the thixotropic modifier comprises nano-silica or fumed silica.

[0009] The present invention preferably selects a mineral composite system with potential activity, namely, a temperature-resistant inorganic curing agent, which can be stably dispersed in a polybasic alkaline solution, exhibits different rheological properties under different shear conditions, and can be cured at a certain temperature to form an inorganic polymer with relatively high strength, thereby developing a high-temperature resistant curable plugging system for sealing and plugging water in heavy oil thermal recovery wells.

[0010] The heat-resistant inorganic curing agent in the plugging system provided by the present invention is selected from at least one of the above three types. Under certain alkaline conditions, the silicon oxygen bond and aluminum oxygen bond of the glass body are broken and repolymerized into tetrahedrons with low polymerization degree. These tetrahedral units are polymerized again to form a three-dimensional network structure with amorphous characteristics similar to polymers. The structural molecules are mainly covalent bonds, have excellent mechanical properties and stability, can withstand high temperatures of 350°C steam, and have extremely low thermal conductivity, which plays a role in isolating the non-heating target layer and improving the thermal utilization rate of steam.

[0011] Suspension stability is the basic performance of the plugging system. The suspension stabilizer improves the settlement stability of the plugging system by increasing viscosity, and also has a positive impact on the seepage characteristics of the system in the steam / water channel.

[0012] After the conventional plugging system enters the steam / water channeling channel, it is diluted during the contact process with the formation water and injected condensed water therein, resulting in reduced viscosity and easy flow, making it difficult to gel and solidify or the strength decreases after solidification, and it cannot withstand subsequent steam injection scouring. How to squeeze the plugging system into and retain it in the steam / water channeling channel is the key to heavy oil thermal recovery channeling and water plugging. The heat-resistant inorganic curing agent and suspension stabilizer in the plugging system of the present invention also have certain thixotropy, but at the same time, the performance of the plugging system is further improved by adding a thixotropic modifier. The three work together to make the plugging system have a strong static thickening shear dilution effect, greatly reduce the viscosity fingering during pumping, selectively enter the large channel of channeling according to the principle of minimizing seepage resistance, quickly generate a network structure to form a pressure-bearing capacity after stopping injection, effectively retain in the target plugging layer, avoid being diluted by formation water before solidification, and effectively avoid spitting out. Moreover, the thixotropic modifier uses nano-SiO2 or fumed silica, which can form hydrogen bonds under low shear conditions, and interact with the tetrahedral units formed by kaolin, slag powder or fly ash in the high-temperature resistant inorganic curing agent, so that the plugging system has a certain spatial network structure, the fluidity is reduced, and the hydrogen bonds are broken under high shear conditions, the fluidity is restored, and the performance is excellent.

[0013] The role of the accelerator is to activate the heat-resistant inorganic curing agent. The mechanism of action is: under high pH conditions, the Si-O bonds of the heat-resistant inorganic curing agent are broken in large quantities, and some of the bridging oxygen bonds are converted into non-bridging oxygen to form an amorphous aluminosilicate compound, which is amorphous to semi-crystalline in structure, [SiO4] 4- The presence of ions accelerates this process.

[0014] It is worth mentioning that slag powder is granulated blast furnace slag powder with grade S95. It is a granular material formed by the reaction of impurities such as silica and alumina in iron ore with lime during blast furnace ironmaking to form a molten material with silicates and aluminosilicates as the main components, which is rapidly cooled after water quenching. It is mainly composed of glass phase, is in a thermodynamically unstable state, has certain potential activity, and is inert under normal conditions, but can be well activated and hydrated in a strong alkaline environment.

[0015] Preferably, the temperature-resistant inorganic curing agent accounts for 15 to 96 wt% of the plugging system, for example, it can be 15 wt%, 24 wt%, 33 wt%, 42 wt%, 51 wt%, 60 wt%, 69 wt%, 78 wt%, 87 wt% or 96 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0016] Preferably, the temperature-resistant inorganic solidifying agent includes metakaolin, slag powder and fly ash.

[0017] Preferably, the mass ratio of metakaolin, slag powder and fly ash in the heat-resistant inorganic curing agent is 0.8-1.2:1.5-2.5:1, the number of metakaolin can be, for example, 0.8, 0.85, 0.89, 0.94, 0.98, 1, 1.03, 1.07, 1.12, 1.16 or 1.2, etc., but is not limited to the listed values, and other values ​​not listed within the range are equally applicable. The number of slag powder can be, for example, 1.5, 1.62, 1.73, 1.84, 1.95, 2, 2.06, 2.17, 2.28, 2.39 or 2.5, etc., but is not limited to the listed values, and other values ​​not listed within the range are equally applicable.

[0018] Preferably, the whiteness value of the metakaolin is 90-95%, for example, 90%, 91%, 92%, 93%, 94% or 95%, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0019] Preferably, the loss on ignition of the metakaolin is less than 0.25%, for example, it may be 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.19%, 0.2%, 0.22%, 0.23% or 0.24%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] It is worth mentioning that metakaolin is an anhydrous aluminum silicate formed by dehydration of kaolin at an appropriate temperature (600-900°C). It contains a large amount of amorphous silicon dioxide and aluminum oxide, is thermodynamically unstable, has high volcanic ash activity, and has gelling properties under appropriate stimulation.

[0021] Preferably, the fineness of the fly ash is ≤25%, for example, it can be 15%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0022] Fly ash is an artificial volcanic ash mixed material formed by high-temperature combustion of coal powder. It itself has little or no hydraulic gelling properties, but when it exists in powder form and water, it can react chemically with calcium hydroxide or other alkaline earth metal hydroxides at room temperature, especially under hydrothermal treatment (steam curing) conditions, to generate compounds with hydraulic gelling properties, becoming a material with increased strength and durability.

[0023] Preferably, the suspension stabilizer comprises bentonite and / or carboxymethyl cellulose.

[0024] Preferably, the content of the suspension stabilizer in the plugging system is 5.0-7.5%, for example, it can be 5.0%, 5.3%, 5.6%, 5.9%, 6.2%, 6.4%, 6.7%, 7%, 7.3% or 7.5%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0025] When the content of the suspension stabilizer in the present invention is low, it is difficult to form a good interaction with the temperature-resistant inorganic curing agent, thixotropic modifier and accelerator, resulting in insufficient suspension stability and easy sedimentation of the system. When the content of the suspension stabilizer is high, the cost is high.

[0026] Preferably, the mass ratio of bentonite to carboxymethyl cellulose in the suspension stabilizer is 2.5 to 6:1, for example, it can be 2.5:1, 2.9:1, 3.3:1, 3.7:1, 4.1:1, 4.5:1, 4.9:1, 5.3:1, 5.7:1 or 6:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0027] The present invention preferably uses a suspension stabilizer composed of bentonite and carboxymethyl cellulose. When the two are used together, the molecules adsorb each other to form a network structure, which effectively reduces the sedimentation rate of solid particles in the slurry and achieves the effect of slurry suspension stability. If only bentonite is used, there are problems of high viscosity and poor rheology. If only carboxymethyl cellulose is used, it is easy to lead to large dosage and high cost.

[0028] Preferably, the bentonite is sodium-based bentonite for drilling mud.

[0029] The main component of bentonite is montmorillonite, which has the property of swelling when in contact with water and can be hydrated into a slurry with a certain viscosity, which plays a role in inhibiting the sedimentation of the dispersed phase of the plugging system. After the bentonite is mixed with water, the water molecules enter the montmorillonite crystal layer, increasing the distance between the crystal layers and increasing the hydration expansion volume several times. When the bentonite is added to the water, there are a certain number of cations between the crystal layers, such as. Sodium-based bentonite has a higher slurrying rate than calcium-based bentonite.

[0030] Preferably, the bentonite technical grade high viscosity carboxymethyl cellulose is CMC-HVT.

[0031] Preferably, the content of the thixotropic modifier in the plugging system is 0.5-1.0%, for example, it can be 0.5%, 0.56%, 0.62%, 0.67%, 0.73%, 0.78%, 0.84%, 0.89%, 0.95% or 1.0%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0032] The content of the thixotropic modifier in the present invention is preferably controlled within the above range, which is more conducive to controlling costs and improving the thixotropy of the system.

[0033] Preferably, the particle size of the nano-silicon dioxide is 50-100 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.

[0034] Preferably, the promoter includes Na2CO3, NaOH and Na2SiO3.9H2O.

[0035] The present invention preferably adopts a combination of the above three to form a promoter. When Na2CO3 is not included, there is a problem of too fast reaction speed. When NaOH is not included, there are problems of slow reaction speed and incomplete reaction. When Na2SiO3·9H2O is not included, there is a problem of low strength after curing. Therefore, the present invention preferably adopts a combination of the above three. The three cooperate with each other to jointly promote the reaction and can make the reaction more thorough, with better effect.

[0036] Preferably, the mass ratio of Na2CO3, NaOH and Na2SiO3·9H2O in the promoter is 0.8-1.2:0.8-1.2:2, the proportion of Na2CO3 can be, for example, 0.8, 0.85, 0.89, 0.94, 0.98, 1, 1.03, 1.07, 1.12, 1.16 or 1.2, etc., but is not limited to the listed values, and other values ​​not listed in the range are equally applicable, and the proportion of NaOH can be, for example, 0.8, 0.85, 0.89, 0.94, 0.98, 1, 1.03, 1.07, 1.12, 1.16 or 1.2, etc., but is not limited to the listed values, and other values ​​not listed in the range are equally applicable.

[0037] The preferred ratio of the accelerator used in the present invention is within the above range, which has a better plugging effect.

[0038] Preferably, the content of the promoter in the plugging system is 2.0-4.0%, for example, it can be 2.0%, 2.3%, 2.5%, 2.7%, 2.9%, 3.2%, 3.4%, 3.6%, 3.8% or 4.0%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0039] Preferably, the aqueous phase comprises formation produced water and / or simulated brine.

[0040] Preferably, the density of the plugging system is 1.1-1.25 g / cm 3 , for example, it can be 1.10 g / cm 3 , 1.12g / cm 3 , 1.14g / cm 3 , 1.15g / cm 3 , 1.17g / cm 3 , 1.19g / cm 3 , 1.2g / cm 3 , 1.22g / cm 3 , 1.24g / cm 3 or 1.25g / cm 3 The above values ​​are not limited to the above values, and other values ​​not listed in the above values ​​are also applicable.

[0041] Preferably, the apparent viscosity of the plugging system is 20 to 35.2 mPa·S, for example, it may be 20 mPa·S, 22 mPa·S, 24 mPa·S, 26 mPa·S, 27 mPa·S, 29 mPa·S, 31 mPa·S, 32 mPa·S, 34 mPa·S or 35.2 mPa·S, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0042] Preferably, the plastic viscosity of the plugging system is 14 to 16 mPa·S, for example, it may be 14 mPa·S, 14.3 mPa·S, 14.5 mPa·S, 14.7 mPa·S, 14.9 mPa·S, 15.2 mPa·S, 15.4 mPa·S, 15.6 mPa·S, 15.8 mPa·S or 16 mPa·S, but is not limited to the listed values, and other unlisted values ​​within the range are equally applicable.

[0043] Preferably, the dynamic shear force of the plugging system is 6 to 8.5 Pa, for example, it may be 6.0 Pa, 6.3 Pa, 6.6 Pa, 6.9 Pa, 7.2 Pa, 7.4 Pa, 7.7 Pa, 8 Pa, 8.3 Pa or 8.5 Pa, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0044] Preferably, the filtration loss of the plugging system is 12.5-13.6 ml, for example, it can be 12.5 ml, 12.7 ml, 12.8 ml, 12.9 ml, 13 ml, 13.2 ml, 13.3 ml, 13.4 ml, 13.5 ml or 13.6 ml, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0045] Preferably, the initial setting time of the plugging system at 70°C is 12 to 36 hours, for example, it can be 12 hours, 15 hours, 18 hours, 20 hours, 23 hours, 26 hours, 28 hours, 31 hours, 34 hours or 36 hours, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0046] Preferably, the final setting time of the plugging system at 70°C is 24 to 84 hours, for example, it can be 24 hours, 31 hours, 38 hours, 44 hours, 51 hours, 58 hours, 64 hours, 71 hours, 78 hours or 84 hours, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0047] Preferably, the volume retention rate of the plugging system at 300° C. for 30 days is above 98%, for example, 98%, 98.5% or 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0048] Preferably, the compressive strength of the plugging system under the condition of curing at 70°C for 14 days is between 2.5 and 3.7 MPa, for example, it may be 2.5 MPa, 2.7 MPa, 2.8 MPa, 2.9 MPa, 3.1 MPa, 3.2 MPa, 3.3 MPa, 3.5 MPa, 3.6 MPa or 3.7 MPa, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0049] Preferably, the gas permeability of the plugging system under the condition of curing at 70°C for 14 days is between 0.02 and 0.12 mD, for example, it may be 0.02 mD, 0.04 mD, 0.05 mD, 0.06 mD, 0.07 mD, 0.08 mD, 0.09 mD, 0.1 mD, 0.11 mD or 0.12 mD, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0050] In a second aspect, the present invention provides a method for preparing the plugging system for sealing wells and blocking water according to the first aspect, the preparation method comprising: mixing materials of the plugging system to obtain the plugging system.

[0051] The preparation method of the plugging system provided in the second aspect of the present invention has a simple process and is easy to manufacture.

[0052] Preferably, the preparation method comprises: first mixing the water phase and the suspension stabilizer, performing a first stirring, then adding the temperature-resistant inorganic curing agent, the thixotropic modifier and the accelerator, and performing a second stirring to obtain a uniform plugging system.

[0053] The present invention preferably mixes the water phase and the suspension stabilizer first, which has the effect of improving the dispersion stability of subsequent materials. If all are directly mixed, there are problems such as sedimentation and agglomeration of the temperature-resistant inorganic curing agent, which is not conducive to uniform dispersion.

[0054] Preferably, the first stirring time is 8 to 15 min, for example, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0055] Preferably, the second stirring time is 15 to 25 min, for example, 15 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0056] In a third aspect, the present invention provides a method for sealing and plugging water from a well, wherein the method for sealing and plugging water from a well adopts the plugging system described in the first aspect.

[0057] The method for sealing and plugging water from a well provided by the present invention can effectively block large steam / water channeling channels, significantly increase oil production, and has an excellent water control and oil production increase effect, especially for sealing and plugging water from a heavy oil thermal recovery well.

[0058] Preferably, the well sealing and water plugging is heavy oil thermal recovery well sealing and water plugging.

[0059] Preferably, the steam temperature for thermal recovery of heavy oil is ≥300°C, for example, it may be 300°C, 310°C, 320°C, 330°C, 340°C or 350°C.

[0060] Preferably, the steam pressure of the heavy oil thermal recovery is 0 to 18 MPa, for example, it can be 0 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 8 MPa, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 15 MPa or 18 MPa.

[0061] Compared with the prior art, the present invention has at least the following beneficial effects:

[0062] (1) The plugging system for plugging wells and blocking water provided by the present invention preferably selects a variety of mineral composite systems with potential activity, can be stably dispersed in a polybasic alkaline solution, exhibits different rheological properties under different shear conditions, and can be solidified at a certain temperature to form an inorganic polymer with high strength, thereby developing a high-temperature resistant and curable plugging system for plugging wells and blocking water in heavy oil thermal recovery;

[0063] (2) The plugging system for plugging well channeling and water blocking provided by the present invention has moderate density, low viscosity before solidification, and is easy to pump. Under the strong thixotropic effect, a hydrogen bond network structure is formed to be retained in the large channel of steam / water channeling, thereby avoiding dilution of formation water and spitting back of the plugging agent. After solidification, it can withstand a temperature of more than 300°C, and its compressive strength can reach more than 3MPa, effectively plugging the large channel of steam / water channeling. The plugging system for plugging well channeling and water blocking prepared is not easy to precipitate, has strong stability, and has excellent thixotropic properties, and can achieve complete plugging;

[0064] (3) The plugging system for well sealing and water blocking provided by the present invention is suitable for sealing and water blocking in heavy oil thermal recovery reservoirs. It can be used alone or in combination with other plugging materials. It has been verified through indoor and field tests that the system has a good effect of controlling water and increasing oil production. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 It is a schematic diagram of the plugging system prepared in Example 1 of the present invention before solidification.

[0066] Figure 2 This is a curve showing the change of the pressure resistance of the plugging system prepared in Example 1 of the present invention over time after curing.

[0067] Figure 3 It is a schematic diagram of the core drilled in Test 3 using the plugging system prepared in Example 1 of the present invention.

[0068] Figure 4 This is a graph showing the change in liquid production over time when the plugging system prepared in Example 1 of the present invention is applied to a heavy oil thermal recovery well before and after plugging water. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0070] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0071] Example 1

[0072] The present embodiment provides a plugging system for sealing wells and blocking water, the plugging system comprising 5% metakaolin, 10% slag powder, 5% fly ash, 5% sodium bentonite, 1% carboxymethyl cellulose, 0.5% nano-SiO2 (particle size range is 50-100nm), 0.5% Na2CO3, 0.5% NaOH, 1% Na2SiO3·9H2O, and the rest is water phase.

[0073] The preparation method of the plugging system comprises: preparing 200 mL (liquid phase density is calculated as 1) of simulated water with a mineralization degree of 2000 mg / L in a 250 mL beaker, slowly adding 10 g of sodium bentonite and 2 g of carboxymethyl cellulose under stirring conditions to make them dispersed evenly, and continuing to stir for 10 minutes; adding 1 g of Na2CO3, 1 g of NaOH, 2 g of Na2SiO3·9H2O, 1 g of nano-SiO2, 10 g of metakaolin, 10 g of fly ash and 20 g of slag powder in sequence under stirring conditions, and continuing to stir for 20 minutes to make them dispersed evenly, so as to obtain the following: Figure 1 The liquid plugging system shown.

[0074] Test 1: Seal the solution-like plugging system and place it in a constant temperature water bath, set the temperature to 70°C, and record the initial setting time and final setting time.

[0075] Test 2: Testing the mechanical properties of the plugging system

[0076] The oil and gas reservoir stress sensitivity tester is used to evaluate the compressive strength of the plugging system. The compressive strength refers to the maximum pressure that a unit area module can withstand without side restraint.

[0077] Prepare the above-mentioned plugging system solution in appropriate amount for use, install the plugging body into a mold and cure it under normal pressure (the curing temperature is set to 70°C, and the curing device is equipped with a stirrer), and carry out the "7 cement stone compressive strength test" in accordance with GB / T19139-2012 "Oil Well Cement Test Method". The test results are shown in the figure below. Figure 2 As shown,

[0078] Test 3: Detect the permeability of the plugging system after curing

[0079] The STY-Ⅱ gas permeability meter is used to detect the permeability of the plugging system after curing. The permeability indicates the ability of the medium to allow fluid to pass through. According to Darcy's law, the gas permeability calculation formula is:

[0080]

[0081] Where: K——gas permeability, md; P0——atmospheric pressure, 0.1MPa; Q0——flow rate under atmospheric pressure, cm 3 / s; μ g ——Gas viscosity, MPa·s; L——Rock sample length, cm; A——Rock sample cross-sectional area, cm 2 ; P1, P2——core inlet and outlet pressure, MPa.

[0082] Experimental conditions: room temperature 20°C, nitrogen gas was used as the displacement medium, nitrogen viscosity was 0.0176mpa.s, and the confining pressure system was set to 0.80MPa.

[0083] The molds were loaded and maintained at normal pressure according to the method of test 2; the modules that had been maintained for 168 hours were taken out and cut into standard cores (Ø25, core columns with a length of not less than 2.5 cm, such as Figure 3 The numbered cores were placed in the STY-Ⅱ gas permeability tester, and the permeability after consolidation was directly tested according to the system setting steps. Each core was tested twice by changing the inlet and outlet ends to obtain the average permeability of the core.

[0084] Test 4: Field Trial

[0085] A group of heavy oil thermal recovery block in Liaohe Oilfield has a total production layer of 284.67m. Before the measures were taken, there were 10 rounds of steam huff and puff (temperature of 300℃, steam pressure of 9.5MPa). The production was normal in the first few rounds, but the steam pressure dropped significantly in the 8th round, and the water content increased significantly at the end of the round. The water recovery rate reached 222%, and the subsequent rounds were high in water content. Analysis showed that the high water content was caused by bottom water intrusion in the well, and water plugging construction was carried out to resume production.

[0086] The well was previously plugged with gel (referred to as the first operation) and the oil production was increased by 106 tons, but the effect was poor. The plugging system provided in Example 1 was used, specifically a three-stage plugging composite water plugging process (referred to as the second operation), and a total of 300m of the plugging system in Example 1 was pumped. 3 The daily liquid and oil production of the field test are as follows: Figure 4 As shown, from Figure 4 It can be seen that after the secondary construction, that is, after adopting the plugging system provided in Example 1, the daily water content decreased significantly, and the daily oil production increased significantly. After the secondary construction, the maximum daily production was 11t, and the average daily production increased by 5.75t, which was 2 times higher than before.

[0087] Example 2

[0088] The present embodiment provides a plugging system for blocking well channeling and water blocking, and the plugging system comprises 4% metakaolin, 7.5% slag powder, 5% fly ash, 4% sodium bentonite, 1.5% carboxymethyl cellulose, 1.0% nano-SiO2, 0.4% Na2CO3, 0.6% NaOH, and S SiO3·9H2O1%, the rest is water phase.

[0089] The preparation method of the plugging system comprises: preparing 200 mL of simulated water with a mineralization degree of 2000 mg / L in a 250 mL beaker, slowly adding sodium bentonite and carboxymethyl cellulose under stirring conditions to make them dispersed evenly, and continuing to stir for 15 minutes; adding Na2CO3, NaOH, Na2SiO3·9H2O, nano-SiO2, metakaolin, fly ash and slag powder in sequence under stirring conditions, and continuing to stir for 25 minutes to make them dispersed evenly, so as to obtain a solution-like plugging system.

[0090] Example 3

[0091] The present embodiment provides a plugging system for sealing wells and blocking water, and the plugging system comprises 6% metakaolin, 12.5% ​​slag powder, 5% fly ash, 6% sodium bentonite, 1% carboxymethyl cellulose, 0.5% nano-SiO2, 0.5% Na2CO3, 0.5% NaOH, and Na S SiO3·9H2O1%, the rest is water phase.

[0092] The preparation method of the plugging system comprises: preparing 200 mL of simulated water with a mineralization degree of 2000 mg / L in a 250 mL beaker, slowly adding sodium bentonite and carboxymethyl cellulose under stirring conditions to make them dispersed evenly, and continuing stirring for 10 minutes; adding Na2CO3, NaOH, Na S SiO3·9H2O, nano-SiO2, metakaolin, fly ash and slag powder are stirred for 20 minutes to disperse them evenly, thus obtaining a solution-like plugging system.

[0093] Example 4

[0094] This embodiment provides a plugging system for sealing wells and blocking water. The plugging system is the same as that of Embodiment 1 except that it does not contain fly ash, and will not be described in detail here.

[0095] Example 5

[0096] This embodiment provides a plugging system for sealing wells and blocking water leakage. The plugging system is the same as that of Embodiment 1 except that it does not contain kaolin, and will not be described in detail here.

[0097] Example 6

[0098] This embodiment provides a plugging system for sealing wells and blocking water flow. The plugging system is the same as that of Embodiment 1 except that it does not contain carboxymethyl cellulose, and will not be described in detail here.

[0099] Example 7

[0100] The present embodiment provides a plugging system for sealing wells and blocking water flow. The plugging system is the same as that of Embodiment 1 except that it does not contain Na2SiO3.9H2O, and will not be described in detail here.

[0101] Example 8

[0102] This embodiment provides a plugging system for sealing wells and blocking water. The plugging system is the same as that of Embodiment 1 except that nano-silicon dioxide is replaced by micron-sized silicon dioxide (1 to 50 μm), and will not be described in detail here.

[0103] Comparative Example 1

[0104] This comparative example provides a plugging system for blocking well channeling and water blocking. The plugging system is the same as Example 1 except that it does not contain nano-SiO2, and will not be described in detail here.

[0105] Comparative Example 2

[0106] This comparative example provides a plugging system for sealing wells and blocking water leakage. The plugging system is the same as Example 1 except that 5% of metakaolin, 10% of slag powder and 5% of fly ash are replaced with 20% of fly ash, and the rest is not repeated here.

[0107] Test method: The test was performed using the test method in Example 1.

[0108] The test results of the above embodiments and comparative examples are shown in Table 1.

[0109] Table 1

[0110]

[0111] From Table 1, we can see the following points:

[0112] (1) It can be seen from Examples 1 to 3 that the plugging system for well channeling and water blocking provided by the present invention can withstand a temperature of more than 300°C after solidification, has a compressive strength of more than 3.2 MPa, can completely block large steam / water channeling channels, shortens the initial / final setting time, has high stability, and is not easy to precipitate;

[0113] (2) It can be seen from Example 1, Examples 4 to 5 and Comparative Example 2 that the combination of fly ash, metakaolin and slag powder is very critical. When one or two of them are missing, the compressive strength of the obtained plugging system at high temperature is significantly reduced. This shows that the present invention improves the compressive strength of the plugging system by selecting a combination of fly ash, metakaolin and slag powder, and the three act synergistically;

[0114] (3) It can be seen from Example 1 and Example 6 that Example 1 contains carboxymethyl cellulose, and compared with Example 6 which does not contain carboxymethyl cellulose, the stability of the plugging system in Example 6 is significantly reduced, and it is easy to precipitate when placed normally, resulting in difficulty in subsequent construction and use. This shows that the plugging system for well channeling and water blocking provided by the present invention is improved by adding carboxymethyl cellulose, which acts together with bentonite as a suspension stabilizer, thereby improving the stability of the plugging system and thus improving its workability;

[0115] (4) From Example 1 and Example 7, it can be seen that Example 7 does not contain Na2SiO3.9H2O, resulting in a low strength of only 2.5 MPa after curing. This shows that the present invention uses a combination of Na2CO3, NaOH and Na2SiO3.9H2O as an accelerator, and the three cooperate with each other to promote the reaction and make the reaction more thorough, resulting in higher strength.

[0116] (5) It can be seen from Example 1, Example 8 and Comparative Example 1 that the nano-scale silica used in Example 1 is much better than the thixotropic performance of Example 8 in comparison with the micron-scale silica used in Example 8 and the absence of silica in Comparative Example 1. This results in poor plugging effect in Example 8, making it difficult to completely plug large channels, and ultimately limited oil extraction effect. In Comparative Example 1, plugging is even impossible. This shows that the present invention has a better thixotropic effect by selecting nano-scale silica as a thixotropic modifier.

[0117] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A plugging system for well sealing and water blocking, characterized in that: The plugging system includes a temperature-resistant inorganic curing agent, a suspension stabilizer, a thixotropic modifier, an accelerator and a water phase; The heat-resistant inorganic curing agent includes any one of metakaolin, slag powder or fly ash, or a combination of at least two thereof; The thixotropic modifier includes nano silicon dioxide or fumed silicon dioxide.

2. The plugging system according to claim 1, characterized in that: The temperature-resistant inorganic curing agent accounts for 15 to 96 wt % of the plugging system; Preferably, the temperature-resistant inorganic curing agent includes metakaolin, slag powder and fly ash; Preferably, the mass ratio of metakaolin, slag powder and fly ash in the heat-resistant inorganic curing agent is 0.8-1.2:1.5-2.5:1; Preferably, the whiteness value of the metakaolin is 90-95%; Preferably, the ignition loss of the metakaolin is less than 0.25%; Preferably, the fineness of the fly ash is ≤25%.

3. The plugging system according to claim 1 or 2, characterized in that: The suspension stabilizer includes bentonite and / or carboxymethyl cellulose; Preferably, the content of the suspension stabilizer in the plugging system is 5.0-7.5%; Preferably, the mass ratio of bentonite to carboxymethyl cellulose in the suspension stabilizer is 2.5 to 6:1; Preferably, the bentonite is sodium-based bentonite for drilling mud; Preferably, the bentonite technical grade high viscosity carboxymethyl cellulose.

4. The plugging system according to any one of claims 1 to 3, characterized in that: The content of the thixotropic modifier in the plugging system is 0.5-1.0%; Preferably, the particle size of the nano-silicon dioxide is 50 to 100 nm.

5. The plugging system according to any one of claims 1 to 4, characterized in that: The accelerator includes Na2CO3, NaOH and Na2SiO3·9H2O; Preferably, the mass ratio of Na2CO3, NaOH and Na2SiO3·9H2O in the accelerator is 0.8-1.2:0.8-1.2:2; Preferably, the content of the accelerator in the plugging system is 2.0-4.0%.

6. The plugging system according to any one of claims 1 to 5, characterized in that: The water phase includes formation produced water and / or simulated brine.

7. The plugging system according to any one of claims 1 to 6, characterized in that: The density of the plugging system is 1.1-1.25 g / cm 3 ; Preferably, the apparent viscosity of the plugging system is 20 to 35.2 mPa·S; Preferably, the plastic viscosity of the plugging system is 14-16 mPa·S; Preferably, the dynamic shear force of the plugging system is 6 to 8.5 Pa; Preferably, the filtration loss of the plugging system is 12.5 to 13.6 ml; Preferably, the initial setting time of the plugging system at 70°C is 12 to 36 hours; Preferably, the final setting time of the plugging system at 70°C is 24 to 84 hours; Preferably, the volume retention rate of the plugging system at 300°C for 30 days is above 98%; Preferably, the compressive strength of the plugging system is 2.5-3.7 MPa under the condition of curing at 70°C for 14 days; Preferably, the plugging system has a gas permeability of 0.02-0.12 mD under curing conditions at 70° C. for 14 days.

8. A method for preparing the plugging system for blocking well channeling and water blocking according to claim 6 or 7, characterized in that: The preparation method comprises: mixing materials of the plugging system to obtain the plugging system.

9. The preparation method according to claim 8, characterized in that: The preparation method comprises: firstly mixing a water phase and a suspension stabilizer, performing a first stirring, then adding a temperature-resistant inorganic curing agent, a thixotropic modifier and an accelerator, performing a second stirring, and obtaining a uniform plugging system. Preferably, the first stirring time is 8 to 15 minutes; Preferably, the second stirring time is 15 to 25 minutes.

10. A method for sealing wells and plugging water, characterized in that: The method for sealing wells and plugging water adopts the plugging system described in any one of claims 1 to 7; Preferably, the well sealing and water plugging is heavy oil thermal recovery well sealing and water plugging.